Comparison of phase-change-heat-pump cooling and liquid cooling for PEM fuel cells for MW-level aviation propulsion. (8th August 2022) - Kösters, Till Lennart; Liu, Xi; Kožulović, Dragan; Wang, Shaofan; Friedrichs, Jens; Gao, Xin
Abstract: Proton exchange membrane fuel cells (PEMFCs) are seen a key player in the sustainable and clean aviation transition. They can supply the main mega-watt (MW) level electric power aboard with many advantages. To notably increase their system specific power, a new phase-change-heat-pump (PCHP) cooling strategy is proposed and compared with the conventional liquid cooling through a model-based study. The comparison is carried out in terms of the induced drag power on a PEMFC-jet hybrid engine layout. The results reveal a drag reduction of 1.528 MW under the PCHP cooling, which accounts for about 16% of the aircraft's net cruise power. This saving is mainly from the minimized capacity of the heat exchanger between the PEMFCs and ambient. Besides, the ramjet effect also contributes significantly in the drag reduction. Last but not least, the optimal operating current density of the PEMFCs under PCHP cooling is brought up by about 26.5%. Graphical abstract: Image 1 Highlights: A novel phase cooling is proposed for an aerospace H2-PEMFC-jet hybrid engine. The engine under the novel cooling and conventional liquid cooling is modeled. PEMFC optimal operating current is raised by 26.5% under the novel cooling. The total engine drag loss is reduced by 23% (1.6 MW) under the novel cooling. The radiator under the novel cooling saves 94% mass of the liquid cooling's.